The Strain to Hold Ground: Site-Based Conflict and an Indigenous Ideology of Water and Place - Heckenberg, Robyn (Springer, 2019)
In terms of duties and obligations, Indigenous peoples hold true to stories about the way to treat and respect the land, the water and the sky, yet globally water and land resources, in particular, have become locations of conflict. The degradation of the rivers, and of the land associated with resourcing water, creates sites of conflict between commercial capitalist ideology and Indigenous utilitarian and spiritual difference. ‘The strain to hold ground’ analyses the clash in ideology between the Australian contemporary colonial state and Indigenous interests and value systems. The research is substantiated by a number of examples of intercultural communication break-down, where the nexus between place and cultural difference manifests as conflict arising from the uneven relationship between the colonised and the coloniser.